The event data management problem: getting the most from network detection and response. Issue 1 (January 2021) - Udipi, Sudhir
Abstract : Detecting cyberthreats has become a big data management challenge. Threat actors employ advanced strategies to hide in hard-to-find places on your network. In order to detect these threats, you must consolidate data from your entire IT environment and analyse it. Many organisations already collect data from multiple sources but still have blind spots in their environment where they don't have visibility. It's time to fill those gaps, argues Sudhir Udipi of Securonix. Detecting cyber security threats has become a big data management challenge. Threat actors employ advanced strategies to hide in hard-to-find places on your network. In order to detect these threats, you must consolidate data from your entire IT environment and analyse it. Many organisations already collect data from multiple sources but still have blind spots in their environment where they don't have visibility.